Genetic Determinants of Immune Cells and Hepatocellular Carcinoma Risk: A Bioinformatics and Bidirectional Mendelian Randomization Study - Tong WU; Fei GAO; Fei TENG; Qiaoli ZHANG (Zhongliu Fangzhi Yanjiu, 2025)
ObjectiveTo identify core targets of hepatocellular carcinoma (HCC) by using bioinformatics and specific algorithms, explore their relationships with immune cells, and investigate the causal relationships between immune cells and HCC through Mendelian randomization. MethodsRelevant genes associated with the development of HCC were screened using the GEO and TCGA databases. Immune infiltration analysis was conducted using GSVA and CIBERSORT algorithms. A bidirectional Mendelian randomization analysis was then performed to explore the causal relationships between immune cells and HCC. ResultsA total of 284 HCC-related genes were identified, with 120 genes recognized within the protein interaction network. Immune infiltration analysis revealed significant correlations between key genes and immune cells. Mendelian randomization results indicated that HLA DR on CD33+ HLA DR+ CD14dim (OR=1.097, 95%CI: 1.002–1.201, P=0.045, PBonferroni=0.091) and CD8 on CD28+ CD45RA+ CD8+ T cell (OR=1.123, 95%CI: 1.027–1.228, P=0.011, PBonferroni=0.022) were the risk factors for HCC. Conversely, HLA DR++ monocyte absolute count was identified as a protective factor for HCC (OR=0.812, 95%CI: 0.702–0.938, P=0.005, PBonferroni=0.139). ConclusionThe occurrence and development of liver cancer may be related to CDK1, CCNB1, and CDC20, showing a high degree of correlation with Th2 cells, T helper cells, Th17 cells, and DCs. Mendelian randomization shows that HLA DR on CD33+HLA DR+ CD14dim and CD8 on CD28+CD45RA+CD8+T cells are associated with an increased risk of HCC. The risk of hepatocellular carcinoma is associated with a decrease in the level of HLA DR++monocyte absolute count.